Effects of banana wilt disease on soil nematode community structure and diversity - ZHONG Shuang; HE Ying-dui; HAN Li-na; ZENG Hui-cai; JIN Zhi-qiang (浙江大学学报. 农业与生命科学版)
To investigate the effect of pathogen causing banana wilt disease on soil ecosystem health, the differences of soil nematode trophic groups and ecological indices between banana wilt disease soil and control soil were compared in Hainan Province using soil nematode as bioindicator. The results showed that 31 nematode genera in the disease area and control area were identified, 26 of which was in disease area, 28 in control area. The abundance of total nematodes, bacterivore in 10-30 cm soil layer and plant parasites and the values of Shannon-Wiener diversity index (H′), maturity index (MI), structure index (SI) and enrichment index (EI) were significantly lower (P<0.01) in the disease area than in the control area, while those of fungivores and Simpson's dominance index (λ) exhibited quite a reverse condition. The abundance of total nematodes and bacterivore decreased (P<0.01) while those of plant parasites and the values of SI increased (P<0.01) with increasing soil depth in the disease area. The abundance of total nematodes and plant parasites decreased (P<0.05) and the values of SI (P<0.01) increased with increasing soil depth in the control area. It is indicated that pathogen causing banana wilt disease changed soil nematode community structure and decreased diversity of soil nematode community.